The expression 1 2 + 2 1 1 + 2 3 + 3 2 1 + … + 9 9 9 9 1 0 0 0 0 + 1 0 0 0 0 9 9 9 9 1 is equal to b a , where a and b are coprime positive integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
mesmerising....................
Oops. Typo. When I say "after we", I mean "so that we".
Can you tell me how to make my fractions bigger like yours ?
Log in to reply
You need to use \ [ \ ] instead of \ ( \ ) .
Additionally, if you want to make your fractions bigger within text, you can use
\dfrac{numerator}{denominator}
For example, I can write 5 3 using frac, but using the dfrac notation, I get 5 3 . Note that this distorts the spacing between lines of text, but if you desire a large fraction and don't care about the spacing, dfrac is the way to go.
Ouch! Another typo! In the penultimate line, the 1000 in the denominator should be a 10,000, that is to say, 1 with 4 zeroes, not 3.
See that, we will simplify the fraction, that is :
∑ i = 1 9 9 9 9 a a + 1 + ( a + 1 ) a 1 = ∑ i = 1 9 9 9 9 a a + 1 + ( a + 1 ) a 1 × ( a + 1 ) a − a a + 1 ( a + 1 ) a − a a + 1 . Implies :
= ∑ i = 1 9 9 9 9 a ( a + 1 ) ( a + 1 ) a − a a + 1 = ∑ i = 1 9 9 9 9 ( a ( a + 1 ) ( a + 1 ) a − a ( a + 1 ) a a + 1 )
= ∑ i = 1 9 9 9 9 ( a 1 − a + 1 1 ) = 1 1 − 1 0 0 0 0 1 = 1 − 1 0 0 1 = 1 0 0 9 9
⟹ a = 9 9 , and b = 1 0 0 . So,
a + b = 9 9 + 1 0 0 = 1 9 9
Let us consider a general term of the following series -
( a + 1 ) ( a ) + ( a ) ( a + 1 ) 1
This can be rationalized to get
( a + 1 ) ( a ) + ( a ) ( a + 1 ) 1 = ( a + 1 ) ( a ) + ( a ) ( a + 1 ) 1 × ( a + 1 ) ( a ) − ( a ) ( a + 1 ) ( a + 1 ) ( a ) − ( ( a ) ( a + 1 ) = ( a ) ( a + 1 ) 2 − ( a ) 2 ( a + 1 ) ( a + 1 ) ( a ) − ( a ) ( a + 1 ) = ( a ) ( a + 1 ) [ ( a + 1 ) − ( a ) ] ( a + 1 ) ( a ) − ( a ) ( a + 1 ) = ( a ) ( a + 1 ) ( a + 1 ) ( a ) − ( a ) ( a + 1 ) = ( a ) ( a + 1 ) ( a + 1 ) ( a ) − ( a ) ( a + 1 ) ( a ) ( a + 1 ) = a 1 − a + 1 1
Now the given series can be written as -
( 1 1 − 2 1 ) + ( 2 1 − 3 1 ) + ( 3 1 − 4 1 ) + … +
( 9 9 9 8 1 − 9 9 9 9 1 ) + ( 9 9 9 9 1 − 1 0 0 0 0 1 )
which, on cancellation reduces to
1 − 1 0 0 1 = 1 0 0 9 9
So the answer is 9 9 + 1 0 0 = 1 9 9
( a b + b a ) 1 = ( a b + b a ) × ( a b − b a ) 1 × ( a b − b a ) = a 2 b − b 2 a ( a b − b a ) = a b ( a − b ) ( a b − b a )
in the above series a-b= -1
so,
a b ( a − b ) ( a b − b a ) = − a b ( a b − b a ) = b − 1 + a 1 and
( 1 2 + 2 1 ) 1 = 2 − 1 + 1 1
( 2 3 + 3 2 ) 1 = 3 − 1 + 2 1
..
..
..
( 9 9 9 9 1 0 0 0 0 + 1 0 0 0 0 9 9 9 9 ) 1 = 1 0 0 0 0 − 1 + 9 9 9 9 1
adding all the terms we get
2 − 1 + 1 1 + 3 − 1 + 2 1 +..........+ 1 0 0 0 0 − 1 + 9 9 9 9 1
= 1- 1 0 0 0 0 1 = 1- 1 0 0 1 = 1 0 0 9 9
Note that
k k + 1 + ( k + 1 ) k 1
= − k ( k + 1 ) k k + 1 − ( k + 1 ) k
= k 1 − k + 1 1
Therefore, the desired sum is equal to 1 − 2 1 + 2 1 − 3 1 + . . . + 9 9 9 9 1 − 1 0 0 0 0 1 = 1 − 1 0 0 0 0 1 = 1 0 0 9 9
Thus, we have a + b = 9 9 + 1 0 0 = 1 9 9
i i + 1 + ( i + 1 ) i 1 = i ( i + 1 ) ( i + 1 ) i − i ( i + 1 ) = i i − i + 1 i + 1 . Thus the given sum is 1 1 − 2 2 + 2 2 − 3 3 + ⋯ + 9 9 9 8 9 9 9 8 − 9 9 9 9 9 9 9 9 + 9 9 9 9 9 9 9 9 − 1 0 0 0 0 1 0 0 0 0 = 1 − . 0 1 = 1 0 0 9 9 , so the answer is 9 9 + 1 0 0 = 1 9 9 .
We first find a generic simplification of each added term. We can write each term in the form
a
a
+
1
+
(
a
+
1
)
a
1
=
a
a
+
1
+
(
a
+
1
)
a
1
⋅
a
a
+
1
−
(
a
+
1
)
a
a
a
+
1
−
(
a
+
1
)
a
=
a
2
(
a
+
1
)
−
(
a
+
1
)
2
a
a
a
+
1
−
(
a
+
1
)
a
. Simplifying,
a
(
a
+
1
0
(
a
+
1
)
a
−
a
a
+
1
. We know separate this fraction into two fractions, getting us
a
(
a
+
1
)
(
a
+
1
)
a
−
a
(
a
+
1
)
a
a
+
1
=
a
1
−
a
+
1
1
.
Thus we find that the sequence telescopes, with terms cancelling out. Now, we can write our series as, with cancelled terms
1
1
−
1
0
0
0
0
1
, which is equal to 99/100. Thus our answer is 99+100=199.
1/[n\sqrt{n+1}+ (n+1)\sqrt{n}] = [(n+1)\sqrt{n} - n\sqrt{n+1}] / [(n+1)\sqrt{n} - n\sqrt{n+1}][n\sqrt{n+1}+ (n+1)\sqrt{n}] = [(n+1)\sqrt{n} - n\sqrt{n+1}] / [(n+1)^2 (n) -n^2 (n+1)] = [(n+1)\sqrt{n} - n\sqrt{n+1}] / [n(n+1)(n+1-n)] = [(n+1)\sqrt{n}] / [n(n+1)] - [n\sqrt{n+1}] / [n(n+1)] = 1/sqrt{n} - 1/sqrt{n+1}
Hence the telescoping sum is actually 1/sqrt{1} - 1/sqrt{2} + 1/sqrt{2}- 1/sqrt{3}+ ...+1/sqrt{9998}- 1/sqrt{9999}+ 1/sqrt{9999} - 1/sqrt{10000} = 1/1 - 1/100 = 99/100.
Therefore a= 99 and b=100. The result follows that a+b = 199.
Let S = 1 2 + 2 1 1 + 2 3 + 3 2 1 + . . . + 9 9 9 9 1 0 0 0 0 + 1 0 0 0 0 9 9 9 9 1
S = n = 1 ∑ 9 9 9 9 n n + 1 + ( n + 1 ) n 1
Rationalizing the denominator,
S = n = 1 ∑ 9 9 9 9 n 2 ( n + 1 ) − ( n + 1 ) 2 ( n ) n n + 1 − ( n + 1 ) n
S = n = 1 ∑ 9 9 9 9 − n ( n + 1 ) n n + 1 − ( n + 1 ) n
S = n = 1 ∑ 9 9 9 9 − n + 1 n + 1 + n n
Expanding,
S = 1 1 − 2 2 + 2 2 − 3 3 + . . . + 9 9 9 9 9 9 9 9 − 1 0 0 0 0 1 0 0 0 0
Simplifying,
S = 1 1 − 1 0 0 0 0 1 0 0 0 0 = 1 − 1 0 0 0 0 1 0 0 = 1 0 0 9 9
Therefore, a + b = 1 9 9 .
Note that each expression is equivalent to 1/(nsqrt(n+1)+(n+1)sqrt(n)), for 1<=n<=9999. 1/(nsqrt(n+1)+(n+1)sqrt(n)) * ((n+1)sqrt(n)-nsqrt(n+1))/((n+1)sqrt(n)-nsqrt(n+1)) =((n+1)sqrt(n)-nsqrt(n+1))/(n(n+1)^2-n^2(n+1)) =((n+1)sqrt(n)-nsqrt(n+1))/(n^2+n) =((n+1)sqrt(n)-nsqrt(n+1))/(n(n+1)) =1/(sqrtn)-1/(sqrt(n+1)). This telescopes, so it is equivalent to 1-1/sqrt(10000)=1-100=99/100. Therefore, the answer is 199.
To get rid of the square roots in the denominator, we use x 2 − y 2 = ( x + y ) ( x − y ) . Therefore, the first term will become 1 2 + 2 1 1 = ( 2 1 ) 2 − ( 1 2 ) 2 1 ∗ ( 2 1 − 1 2 ) = 4 − 2 1 ∗ ( 2 1 − 1 2 ) = 1 ∗ 2 1 ∗ ( 2 1 − 1 2 ) = 1 1 − 2 2 .
Using the same steps, the second term will be 2 2 − 3 3 and the third term will be 3 3 − 4 4 and so on......
Then, by cancelling out the positive and negative fractions which are the same, the expression will be :
1 1 − 2 2 + 2 2 − 3 3 + 3 3 − 4 4 . . . + 9 9 9 9 9 9 9 9 − 1 0 0 0 0 1 0 0 0 0
= 1 1 − 1 0 0 0 0 1 0 0 0 0
= 1 − 1 0 0 1 = 1 0 0 9 9 .
So, a = 9 9 , b = 1 0 0 , a + b = 1 9 9 .
Let n = 9 9 9 9 . The given expression is
r = 1 ∑ n r r + 1 + ( r + 1 ) r 1 = r = 1 ∑ n r 2 ( r + 1 ) − ( r + 1 ) 2 r r r + 1 − ( r + 1 ) r
r = 1 ∑ n r ( r + 1 ) ( r − r − 1 ) r r + 1 − ( r + 1 ) r = r = 1 ∑ n r 1 − r + 1 1
Writing down a few terms,
r = 1 ∑ n r 1 − r + 1 1 = 1 − 2 1 + 2 1 − 3 1 + 3 1 − . . . . . . . . − 1 0 4 1
We notice that most of the terms cancel and we are left with
1 − 1 0 4 1 = 1 − 1 0 0 1 = 1 0 0 9 9
Hence, the answer is 9 9 + 1 0 0 = 1 0 0 .
Haha, 99 + 100 is not 100 :P
Nth term =
(n sqrt(n+1)+(n+1) sqrt(n))
(n+1)*sqrt(n)-n*sqrt(n+1)
= -------------------------------------------------------------------------
(n
sqrt(n+1)+(n+1)
sqrt(n))* ((n+1)
sqrt(n)-n
sqrt(n+1))
(n+1)
sqrt(n)-n
sqrt(n+1))
= -----------------------------------------
((n+1)^2)
n-(n^2)
(n+1)
(n+1)*sqrt(n)-n*sqrt(n+1)
= ----------------------------------------------
(n^3)+2*(n^2)+n –(n^3) –(n^2)
(n+1) sqrt(n)-n sqrt(n+1) = ---------------------------------------- n*(n+1)
= 1/sqrt(n) – 1/sqrt(n+1)
So, 1st term = 1/1 – 1/sqrt(2) 2nd term = 1/sqrt(2) - 1/sqrt(3)
……………………………………………….. and so on 9999th term = 1/sqrt(9999) – 1/sqrt(10000)
Adding we get Total Sum of the series = 1- 1/sqrt(10000) = 1-1/100=99/100 So the answer is 99+100, i.e. 199.
We claim that $\sum_{i=1}^{k^{2}-1}\frac{1}{i\sqrt{i+1}+(i+1)\sqrt{i}}=1-\frac{1}{k}, \forall k\in\mathbb N$ So the aum above is $\frac{99}{100}.$
Base case: $i=1$, so that $\frac{1}{2+\sqrt{2}}=\frac{\frac{1}{1+\sqrt{2}}}{\frac{2+\sqrt{2}}{1+\sqrt{2}}}=\frac{\sqrt{2}-1}{\sqrt{2}}=1-\frac{1}{\sqrt{2}}$
Inductive step. Let the problem to be true for $i=n-1,$ so that $\sum_{i=1}^{n-1}\frac{1}{i\sqrt{i+1}+(i+1)\sqrt{i}}=1-\frac{1}{\sqrt {n}}.$
For $i=n+1$ it is sufficient to prove that $1-\frac{1}{\sqrt{n}}+\frac{1}{n\sqrt{n+1}+(n+1)\sqrt{n}}=1-{1}{\sqrt{n+1}},$ or \frac{1}{\sqrt{n}}-{1}{\sqrt{n+1}}=\frac{1}{n\sqrt{n+1}+(n+1)\sqrt{n}}.$ But $\frac{1}{\sqrt{n}}-{1}{\sqrt{n+1}}=\frac{\sqrt{n+1}-\sqrt{n}}{\sqrt{n(n+1)}}$ and $(\sqrt{n+1}-\sqrt{n})(n\sqrt{n+1}+(n+1)\sqrt{n})=n(n+1)+(n+1)\sqrt{n(n+1)}-n\sqrt{n(n+1)}-n(n+1)=\sqrt{n(n+1)},$ so \frac{\sqrt{n+1}-\sqrt{n}}{\sqrt{n(n+1)}}=\frac{1}{n\sqrt{n+1}+(n+1)\sqrt{n}}.$ This completes the proof.
The expression can be expressed as i = 1 ∑ 9 9 n n + 1 + ( n + 1 ) n 1 . Multiply the denominator and numerator by ( n + 1 ) n − n n + 1 and we will get i = 1 ∑ 9 9 n ( n + 1 ) ( n + 1 ) n − n n + 1 = i = 1 ∑ 9 9 n n − n + 1 n + 1 (We get the denominator using difference of squares). Since this is a telescoping sum, the intermediate terms cancel and we get 1 − 1 0 0 1 = 1 0 0 9 9 .
Whenever you see a irrational denominator try to rationalize it (most commonly done by multiplying by the conjugate of the denominator). By rationalizing the first fraction we get [2-sqrt(2)]/2, then if we add the second term and rationalize the answer we obtain [3-sqrt(3)]/3. Thus we notice a pattern emerging. The sum of (n-1)th terms is given by [n-sqrt(n)]/n. Therefore the last term is 10000-sqrt(10000) all divided by 10000 = 99/100. Therefore a = 99 and b = 100 (satisfying the condition that a and b are coprime positive integers) therefore a+b = 99+100 = 199.
Here, T(n) = 1/[n.root(n+1) + (n+1).rootn] = 1/rootn - 1/root(n+1). (Using key techniques) by telescopic calculation we get s(n) = 1-1/100 = 99/100 a=99, b= 100 a + b = 99 + 100 = 199, which is the solution
1/(1√2+2√1) Can be simplified as (2√1−1√2)/(4−2)=√1−1/√2. similarly 1/(2√3+3√2) can be simplified as (3√2−2√3)/(18−12)=1/√2−1√3 Hence we observe that its a repetition in which each cluster(eg 1/√2) occurs twice in alternating sign in the summation, except the first number in the sequence and the last number the last number is -9999√10000/(10000∗10000∗9999 −9999∗9999∗10000) = −1/√10000= −1/100, Therefore by telescopic summation the final answer is 1−1/100= 99/100, in which 99 and 100 are co-prime so a=99 and b=100, Hence a+b=199 .
Tools needed to solve this problem:
Main Idea :
Determine the General Form .
Analyse it and break it to the form: f ( n ) − f ( n + 1 )
Then we can obtain something like: f ( 1 ) − f ( 2 ) + f ( 2 ) − f ( 3 ) + f ( 3 ) − f ( 4 ) + . . . + f ( n ) − f ( n + 1 )
The answer to the problem will be
f ( 1 ) − f ( n + 1 )
Solution
Determine the General Form
By observing, the General Form is
n n + 1 + ( n + 1 ) n 1
Analyse
Now, we will to remove the square roots in the denominator
n n + 1 + ( n + 1 ) n 1
= n 2 ( n + 1 ) − ( n + 1 ) 2 n n n + 1 − ( n + 1 ) n
= n ( n + 1 ) ( n − n − 1 ) n n + 1 − ( n + 1 ) n
= − n ( n + 1 ) n n + 1 − ( n + 1 ) n
= n ( n + 1 ) ( n + 1 ) n − n n + 1
= n ( n + 1 ) ( n + 1 ) n − n ( n + 1 ) n n + 1
= n n − n + 1 n + 1
Or you may prefer
= n 1 − n + 1 1
Thus,
i = 1 ∑ 9 9 9 9 n 1 − n + 1 1
= 1 − 1 0 0 0 0 1
= 1 − 1 0 0 1
= 1 0 0 9 9
Hence, a + b = 1 9 9
We observe that each term is of the form
n n + 1 + ( n + 1 ) n 1 . We need to simplify this.
Rationalizing and simplifying
n 2 + n ( n + 1 ) n − n n + 1 = n ( n + 1 ) ( n + 1 ) n − n n + 1 = n 1 − n + 1 1
Thus we get a simplified version. So the given expression becomes
[ 1 1 − 2 1 ] + [ 2 1 − 3 1 ] + . . . . . . . + [ 9 9 9 9 1 − 1 0 0 0 0 1 ]
All the terms except first and the last is canceled out as negative fraction of one term cancel out the positive term of other. So above expression is equal to
1 1 − 1 0 0 0 0 1
= 1 − 1 0 0 1 = 1 0 0 9 9
Thus we get our requires answer as 9 9 + 1 0 0 = 1 9 9
Note that i i + 1 + ( i + 1 ) i 1 = i ( i + 1 ) ( i + 1 ) i − i i + 1 = i i + 1 i + 1 − i = i 1 − i + 1 1 Hence i = 1 ∑ 9 9 9 9 i i + 1 + ( i + 1 ) i 1 = i = 1 ∑ 9 9 9 9 ( i 1 − i + 1 1 ) = 1 1 − 1 0 0 0 0 1 = 1 0 0 9 9 Thus a + b = 1 9 9
r = 1 ∑ 9 9 9 9 r r + 1 + ( r + 1 ) r 1
= r = 1 ∑ 9 9 9 9 ( r + 1 ) 2 r − r 2 ( r + 1 ) ( r + 1 ) r − r r + 1
= r = 1 ∑ 9 9 9 9 r ( r + 1 ) ( r + 1 ) r − r r + 1
= r = 1 ∑ 9 9 9 9 ( r 1 − r + 1 1 )
= 1 1 − 9 9 9 9 + 1 1
= 1 0 0 9 9
( n × n + 1 ) + ( ( n + 1 ) × n ) 1
= n × n + 1 × ( n + 1 + n ) 1
= n × n + 1 × ( n + 1 + n ) × ( n + 1 − n ) ( n + 1 − n )
= n × n + 1 ( n + 1 − n )
= n 1 − n + 1 1
By using the method of Telescoping Series , we get
1 1 − 1 0 0 0 0 1 = 1 − 1 0 0 1 = 1 0 0 9 9
Hence we get, a = 9 9 , b = 1 0 0 Therefore a + b = 1 9 9
By rationalizing the fractions, we find that the expression actually telescopes.
1 2 + 2 1 1 + 2 3 + 3 2 1 + . . . + 9 9 9 9 1 0 0 0 0 + 1 0 0 0 0 9 9 9 9 1
= 1 × 2 2 1 − 1 2 + 2 × 3 3 2 − 2 3 + . . . + 9 9 9 9 × 1 0 0 0 0 1 0 0 0 0 9 9 9 9 − 9 9 9 9 1 0 0 0 0
= 1 1 − 2 2 + 2 2 − 3 3 + . . . + 9 9 9 9 9 9 9 9 − 1 0 0 0 0 1 0 0 0 0
= 1 − 1 0 0 0 0 1 0 0 0 0
= 1 − 1 0 0 1
= 1 0 0 9 9
Thus, b a = 1 0 0 9 9 , and a + b = 1 0 0 + 9 9 = 1 9 9
We can rewrite 1/{a\sqrt{a+1}+(a+1)\sqrt{a}} as 1/\sqrt{a}-1/\sqrt{a+1} so it telescopes and we get 1/1-1/100=99/100 for answer of 199
The expression k k + 1 + ( k + 1 ) k 1 is too ugly. So, we use the identity a 2 − b 2 = ( a + b ) ( a − b ) to simplify the expression.
Note that k k + 1 + ( k + 1 ) k 1 = k 2 ( k + 1 ) − k ( k + 1 ) 2 k k + 1 − ( k + 1 ) k = k ( k + 1 ) k k + 1 − ( k + 1 ) k = k k − k + 1 k + 1 = k 1 − k + 1 1 .
Then the sum telescopes perfectly to 1 − 1 0 0 0 0 1 = 1 0 0 9 9 .Thus, a + b = 1 9 9 .
rationalise the denominator and factorise the expression for the nth term you will get 1/(n)^1/2-1/(n+1)^1/2. using telescopic summation you shall get 1-1/100=99/100, a+b=99+100=199
It's pretty simple. All you need to do is reduce the series into a telescopic one, i.e., one with alternating positive and negative signs. First, recognize the general rth term, which is (r sqrt(r+1) + sqrt(r) (r+1))^-1; then what you gotta do is manipulate a little. Taking common factors, you get, [ sqrt(r) sqrt(r+1) { sqrt(r) + sqrt(r+1) } ]^-1. Multiply numerator and denominator by sqrt(r) + sqrt(r+1) to get rid of the radical, and split into two fractions. You'll end up with Tr = [(sqrt(r))^-1] - [sqrt(r+1))^-1]. On summing up till n terms, except for first and last term, all the other terms get cancelled out. Therefore, sum is 1 - [sqrt(n+1))^-1]. Substituting n as 10000 from the above problem, you get the required answer.
Looking at the terms of the sum, we notice that all the terms are of the form a a + 1 + ( a + 1 ) a 1 , where a = 1 , 2 , 3 , … , 9 9 9 9 .
By rationalizing the fraction and manipulating it, we eventually get it into the form:
a a + 1 + ( a + 1 ) a 1
= a 2 ( a + 1 ) − ( a + 1 ) 2 a a a + 1 − ( a + 1 ) a
= a 3 + a 2 − a ( a 2 + 2 a + 1 ) a a + 1 − ( a + 1 ) a
= a 3 + a 2 − a 3 − 2 a 2 − a a a + 1 − ( a + 1 ) a
= − a 2 − a a a + 1 − ( a + 1 ) a
= a 2 + a ( a + 1 ) a − a a + 1
= a ( a + 1 ) ( a + 1 ) a − a a + 1
= a ( a + 1 ) ( a + 1 ) a − a ( a + 1 ) a a + 1
= a a − a + 1 a + 1
= a 1 − a + 1 1
Therefore, by changing each term of the sum into the final form above, we get a telescoping sum:
1 2 + 2 1 1 + 2 3 + 3 2 1 + ⋯ + 9 9 9 9 1 0 0 0 0 + 1 0 0 0 0 9 9 9 9 1
= 1 1 − 2 1 + 2 1 − 3 1 + ⋯ + 9 9 9 8 1 − 9 9 9 9 1 + 9 9 9 9 1 − 1 0 0 0 0 1
= 1 1 − 1 0 0 0 0 1
= 1 − 1 0 0 1
= 1 0 0 9 9
Thus, a + b = 9 9 + 1 0 0 = 1 9 9
The values can be rewritten as functions of n .
f ( n ) = n n + 1 + ( n + 1 ) n 1
A summation can be used to find the sum of the expression from n = 1 to n = 9 9 9 9 .
n = 1 ∑ 9 9 9 9 f ( n ) n = 1 ∑ 9 9 9 9 n n + 1 + ( n + 1 ) n 1 = 1 0 0 9 9
So 1 0 0 9 9 = b a , where a = 9 9 and b = 1 0 0 . a + b = 9 9 + 1 0 0 = 1 9 9
Yes but how did you evaluate the summation?
Multiply f ( n ) by n n + 1 − ( n + 1 ) n n n + 1 − ( n + 1 ) n , so f ( n ) = n 2 ( n + 1 ) − ( n + 1 ) 2 ( n ) n n + 1 − ( n + 1 ) n which can then be split into f ( n ) = n 2 ( n + 1 ) − n ( n + 1 ) 2 n n + 1 − n 2 ( n + 1 ) − n ( n + 1 ) 2 ( n + 1 ) n f ( n ) = − n ( n + 1 ) n n + 1 + n ( n + 1 ) n ( n + 1 ) Rationalize and simplify, f ( n ) = n 1 − n + 1 1 The summation can then be recognized as a telescoping series .. ( 1 1 − 2 1 ) + ( 2 1 − 3 1 ) + . . . + ( 9 9 9 9 1 − 1 0 0 0 0 1 ) Cancel out all the inside fractions and you get 1 1 − 1 0 0 0 0 1 = 1 − 1 0 0 1 So ultimately, n = 1 ∑ 4 0 0 f ( n ) = 1 0 0 9 9
I pointed this out on your solution to the other problem as well; you must make it clear how you evaluated this summation, or your solution isn't really a solution at all.
Log in to reply
you must make it clear how you evaluated this summation, or your solution isn't really a solution at all.
I thought she did make it clear.
Log in to reply
She made it clear after I wrote my comment.
Log in to reply
Problem Loading...
Note Loading...
Set Loading...
Let us first write the sum in summation notation, after we receive a little inkling of what should come next.
k = 1 ∑ 9 9 9 9 k k + 1 + ( k + 1 ) k 1
Let us closely examine the fraction k k + 1 + ( k + 1 ) k 1 . If we multiply both the numerator and the denominator by k k + 1 − ( k + 1 ) k , we obtain
( k 2 ) ( k + 1 ) − ( k + 1 ) 2 ( k ) k k + 1 − ( k + 1 ) k − k 2 + k k k + 1 − ( k + 1 ) k k k − k + 1 k + 1
Isn't that beautiful? Our sum now decomposes into two very simple quantities.
k = 1 ∑ 9 9 9 9 k k + 1 + ( k + 1 ) k 1 = k = 1 ∑ 9 9 9 9 k k − k + 1 k + 1 = k = 1 ∑ 9 9 9 9 k k − k = 1 ∑ 9 9 9 9 k + 1 k + 1 = ( 1 1 + 2 2 … 9 9 9 9 9 9 9 9 ) − ( 2 2 + 3 3 . . . 1 0 0 0 0 1 0 0 0 0 ) = 1 1 − 1 0 0 0 0 1 0 0 0 0 = 1 0 0 0 1 0 0 0 0 − 1 0 0 = 1 0 0 9 9
Our desired sum is 1 9 9 .